Análise técnico-econômica da cunhã em função de lâminas de água e adubação fosfatada no vale do curu, Ceará - Salgado, Eveline Viana (2008)
This study had as its objective to study the effect of water depths and phosphorus levels and their interaction on productivity and economic components of the production cunhã (Clitoria ternatea L.). The experiment was conducted at the Curu Valley Experimental Farm in Pentecoste - Ceará in the period of september 2007 to March 2008. The experimental design was in randomized blocks with split plots, composed of four primary treatments in the plots, four secondary treatments in subplots and four blocks. The treatments is the combination of four irrigation depths (W1 = 615.2 mm; W2 = 605.1 mm; W3 = 540.6 mm; W4 = 365.6 mm) with four levels of phosphate fertilizer (P0 = 0; P1 = 150; P2 = 300; P3 = 450 kg ha-1de P2O5). The crop was established in the field in the spacing of 0.40 m x 0.40 m, being irrigated by a conventional spraying system (Line Source Sprinkler System), with frequency of five days. As results, the factor of production water influenced to a significance level of 1.3% the forage green mass, however, the factor of production phosphorus and the interaction between the two factors showed no significant difference between treatments at 5% level of probability. The maximum yield was estimated 73726.7 kg ha-1mm-1, obtained with the application of 700.4 mm of water and 86.74 kg ha-1 phosphorus. The factor of production water had been limiting the efficiency of cunha, that is not happening with the factor of production phosphorus. The average productivity of water presented no change to the levels of phosphorus, the same occurred with the water depths exceeding 540 mm.